Population Dynamics of Pod Borers on Pigeonpea (Cajanus cajan (L) Millsp.) in Relation to Abiotic Factors - Sreekanth, M.; Ratnam, M.; Ramana, M. V. (International Journal of Bio-resource and Stress Management, 2020)
The experiment conducted at Regional Agricultural Research Station, Lam farm, Guntur, Andhra Pradesh, India during 2015-16 on pigeonpea, Cajanus cajan on population buildup and seasonal abundance of gram pod borer, Helicoverpa armigera and spotted pod borer, Maruca vitrata revealed that peak male moth catches of H. armigera (8.0 moths trap-1 week-1) were observed during 47th SMW (Nov.19 – 25), which coincides with flower bud initiation stage whereas, peak male moth catches of S. litura were observed twice (99.3 and 78.0 moths trap-1 week-1, respectively) at 45th SMW (Nov. 5-11) and 50th SMW (Dec. 10-16). The larval population of both H. armigera and M. vitrata was more during 48th SMW (Nov. 26-Dec.2), which coincides with peak flowering stage of the crop, which recorded 5.2 and 15.6 larvae plant-1 week-1, respectively, which coincides with peak flowering stage of the crop. Highly significant correlation was observed between pheromone trap catches of H. armigera and rainfall, rainy days, sunshine and wind speed with correlation coefficient (r) being 0.576, 0.649, -0.528 and 0.685, respectively. Similarly, highly significant correlation was observed between RH I and RH II with larval population of H. armigera with correlation coefficients (r) being 0.503 and 0.777, respectively. Further, highly significant correlation was observed between RH II and larval population of M. vitrata with correlation coefficient (r) being 0.919. The farmers need to be vigilant so as to optimize the application of insecticides in order to check the pest population from reaching the economic threshold level.